Effects of commercial oligosaccharides on growth of selected beneficial and non-beneficial gut bacteria of broilers - Wong, L. L.; Sieo, Chin Chin; Ramasamy, K.; Ho, Yin Wan (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Prebiotics, which are digestive-resistant low molecular weight oligosaccharides, have been known to able to selectively promote the growth of beneficial bacteria. It is one of the substances that is currently being studied as feed supplement to improve the growth performance of chickens. Several commonly known oligosaccharides that are well documented as prebiotics are such as inulin (INU), isomaltooligosaccharides (IMO), xylooligosaccharides (XOS), nigerooligosaccharides (NOS) and gentioologosaccharides (GOS). Although some of these oligosaccharides have been reported to enhance the growth of beneficial bacteria, the effects on non-beneficial bacteria is limited. Therefore, in the present study, the effects of XOS, IMO, GTO, INU and FOS on the growth of six strains of Lactobacillus and three strains of non-beneficial bacteria (Escherichia coli, Salmonella typhimurium and Salmonella enterica) were investigated. It was observed that only IMO supported the growth of all the tested Lactobacillus spp. Other prebiotics only supported selected strains. Interestingly, the three non-beneficial bacteria were also able to grow in all the tested prebiotics, except inulin. This may indicate that inulin is a more superior prebiotic in comparison to the other tested candidates.